STATE INVESTMENT POLICY AS A TOOL FOR THE RESTORATION AND DEVELOPMENT OF SOCIAL HOUSING IN THE CONTEXT OF NATIONAL SECURITY - SAMOILENKO, Bohdan; LYASHENKO, Oksana; ZUBKO, Vitaliy; LEBEDYNSKA, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the issue of investment policy in social housing as a crucial factor in enhancing the country’s national security. The results of the study show that providing social housing in Ukraine is not just a social initiative or a humanitarian challenge, but a strategic tool for stabilizing social and labor relations (by the way, not only during the war, but also in the post-war period). Housing security is of crucial importance, since its absence hinders employment, discourages people from returning, and, accordingly, slows down effective economic recovery. It is noted that, despite significant differences in the housing policies of individual EU member states’ governments, most of them still share a common feature: the desire to balance social protection with a motivation system. The main incentive is the transfer of social housing for rent, rather than ownership, which encourages tenants to make their own efforts to improve living conditions and, in turn, allows them to assist a broad range of people belonging to socially vulnerable groups within the population. It has been determined that, in conditions of military aggression, migration processes, and infrastructure destruction (i.e., those that pose a threat to national security), the state’s investment policy is a critically essential and strategic tool for ensuring the effective restoration and sustainable development of the social housing fund. It has been established that state investment policy under such conditions can be considered adequate only when it is reoriented from classical economic goals to achieving social stability and resilience in relatively safe regions. It has been proven that, although social housing is not aimed at generating a profit, it still has significant investment potential for the economy and the state, as it creates positive externalities and stimulates the development of related industries. It is substantiated that investments in social housing, which significantly affect the satisfaction of the basic needs of socially vulnerable groups of the population, acquire the status of critical security investments.